Effect of labour market changes on HR functions - Héder Mária; Szabó Szilvia; Dajnoki Krisztina (Anali Ekonomskog fakulteta u Subotici, 2018)
Simultaneously with social, economic transformation, management of the human factor in the world of labour has become increasingly important. People as resources are essential for the effective management of every company; the changing environment requires rational management of resources. The impact of changes within the labour market observed in our time is the strongest on the field of human resource management. The importance of effective workforce management has increased considerably, which raised the significance of human resource professionals and their activities and demanded a certain change in attitude. The impact of globalisation and the lack of workforce and talent also affected the development of HR functions. Besides so-called conventional functions appearing in every organisation irrespective of its organisational size and activity, new areas of activity have been constantly emerging over the past decades, responding to changes in macro-and micro-environment. In our present study, we highlight the characteristics and significance of HR branding, retention, knowledge, competence, talent and flow management from amongst the new trends.